Uniportal Video-Assisted Anatomical Lung Volume Reduction Surgery in Severe Emphysema - Merhej, Hayan; Saipbaev, Akylbek; Nakagiri, Tomoyuki; Selman, Alaa; Golpon, Heiko; Goecke, Tobias; Zardo, Patrick (The Thoracic and Cardiovascular Surgeon, 2025)
Lung volume reduction surgery (LVRS) is an important treatment option for patients with advanced emphysema and is typically performed in a non-anatomical fashion. This study reports the outcome of anatomical LVRS by means of uniportal video-assisted thoracoscopic surgery (VATS).We retrospectively evaluated patients who underwent anatomical LVRS between June 2017 and September 2023 at our institution. Patient characteristics, including demographic data, lung function, as well as morbidity and mortality, were extracted from hospital records.A total of 44 patients (17 males, 38.6%) underwent anatomical LVRS at our institution during the observation period. The preoperative forced expiratory volume per second (FEV1) and FEV1% were 35.4 ± 20.0% and 45.7 ± 18.2%, respectively. Lobectomy was performed in 37 patients (84.1%), while segmentectomy was performed in 10 patients (22.7%, duplicated). Postoperative FEV1 and FEV1% significantly improved compared to preoperative values at the initial follow-up (11.8 ± 6.9 months after the operation): 38.3 ± 19.5%, p < 0.002 and 49.4 ± 18.4%, p < 0.01, respectively. Unfortunately, two patients (4.5%) died within 30 days postoperation. A further follow-up lung function test was performed in 25 patients (56.8%) at 33.1 ± 13.8 months after the operation, showing that FEV1 and FEV1% remained similar to the preoperative values (33.9 ± 20.7%, p = 0.10 and 45.3 ± 18.1%, p = 0.06, respectively).Anatomical lung resection via uniportal VATS is an effective procedure for LVRS in patients with severe emphysema and is associated with acceptable morbidity and mortality.
Keywords: emphysema; bullae; thoracoscopy; VATS; pulmonary function